Unlocking the dermocosmetic potential of winery by-products with liposomal delivery as a key enabler to enhance functional efficacy - Silvia Rodrigo-Gallego; María del Carmen Villegas-Aguilar; Francisco Javier Leyva-Jiménez; M. Elena Alañón (Trends in Food Science & Technology, 2026)

Advances and perspectives in modern geostatistics for energy, natural resources, and environmental studies - Dario Grana; Leonardo Azevedo; Jo Eidsvik; J. Jaime Gómez-Hernández; Alessandra Menafoglio; Joao Narciso; Javier Rodrigo-Ilarri; Amilcar Soares; Valeria Todaro; Andrea Zanini (Earth-Science Reviews, 2026)

Dynamic oceans, shifting priorities: Conservation planning for large pelagic species in a variable Eastern Pacific Ocean - Aura Buenfil-Ávila; Sofía Ortega-García; Héctor Villalobos; Ulianov Jakes-Cota; Rodrigo Moncayo-Estrada; Arelly Ornelas-Vargas; Javier Nori (Ocean & Coastal Management, 2026)

Dormancy dynamics in Japanese plum: transcriptomic responses to variable climatic conditions and chilling requirements - Sara Herrera; José Ignacio Hormaza; Guillem Ylla; Javier Rodrigo; Jorge Lora (Planta, 2026)
Main conclusion Climate exerted a stronger influence than dormancy stage on gene expression in Japanese plum, revealing climate- and genotype-specific regulatory patterns underlying dormancy control and climate adaptation. Abstract Dormancy progression in temperate fruit trees is highly sensitive to environmental conditions and chilling accumulation. To investigate the regulation of dormancy in Japanese plum ( Prunus sali cina hybrids), we performed a comparative transcriptomic analysis of flower buds from two Japanese plum cultivars with different chilling requirements, "Hiromi Red" (high chill) and "Crimson Glo" (low chill), grown under contrasting climates (semi-arid and Mediterranean subtropical). This study combined phenological observations, quantification of chill and heat requirements, as well as transcriptomic analyses across three key developmental stages: full dormancy (T0), dormancy release (T1), and full recovery (T2). Climate exerted a stronger influence than dormancy stage on gene expression profiles, leading to cultivar- and climate-specific transcriptional responses. Key dormancy-related genes—such as DAM , FT , and SAP1 — exhibited differential expression patterns across climates, suggesting potential roles in climatic adaptation. Notably, dormancy phases occurred approximately one month later under Mediterranean subtropical conditions, and were accompanied by a marked reduction in chilling requirements. Expression and phylogenetic analyses revealed that environmental conditions had a stronger effect on the transcriptomic profiles than the progression of dormancy itself, potentially due to epigenetic modulation. These findings provide new insights into the molecular mechanisms underlying dormancy in woody perennial species and offer perspectives for developing cultivars better adapted to changing climatic scenarios.

Celtis guatemalensis (Cannabaceae: Celtis subg. Celtis), a new tree species from the highlands of Guatemala, with an updated key for Celtis of Mexico and Central America - Knut Eisermann; Henrique Borges Zamengo; Débora Cintia Chamorro; Claudia Avendaño-Mendoza; Rodrigo Faleiro de Lima; Ana Barrios; Luis Javier Aju; Sofía Cabañas (Kew Bulletin, 2026)

Small-scale aquaculture as a complementary strategy for small-scale fisheries: A case study of technology adoption in Chile - José Bakit; Mario Jorquera; Constantino Villarroel; Andrés Hurtado; Germán Lira; Rodrigo Rojas; Sebastian Villasante; Javier Seijo; Angelo Araya-Piñones (Fisheries Research, 2026)

The first Large Flake Acheulean in Europe at Revilleja de Valparaíso site, Hortigüela, Spain - Francisco-Javier García-Vadillo; Eudald Carbonell; Xosé-Pedro Rodríguez-Álvarez; Alfonso Benito-Calvo; Régis Braucher; Davinia Moreno; Isabel Hernando-Alonso; Rodrigo Alonso-Alcalde; Marta Navazo-Ruiz; Antoni Canals-Salomó (Quaternary Science Reviews, 2026)

A Drier Year Markedly Enhances Methane, but Not Carbon Dioxide, Emissions in a Mediterranean Reservoir - Cintia L. Ramón; Isabel Reche; Rodrigo J. Gonçalves; Andrés Martínez‐García; Miriam García‐Alguacil; Sergio López‐Padilla; Javier Herrero; Rafael Morales‐Baquero; Enrique P. Sánchez‐Cañete; Alicia Cortés; Sara Valiente; Francisco J. Rueda (Global Change Biology, 2026)
Reservoirs are increasingly recognized as important sources of greenhouse gases (GHGs), yet the temporal scales and environmental drivers governing CO 2 and CH 4 flux variability remain poorly constrained. This is particularly the case for Mediterranean systems, which are subject to strong hydrological variability. Here, we present and analyze year‐round, high‐frequency eddy covariance measurements of CO 2 and CH 4 fluxes in a Mediterranean reservoir over two years with contrasting hydrological conditions, explicitly evaluating variability at diurnal, multiday, and seasonal timescales. The reservoir acted as a net source of both gases in both years, but CH 4 fluxes exhibited substantially greater temporal variability than CO 2 fluxes. The seasonal component dominated CH 4 flux variability (> 75%), with annual areal fluxes and reservoir‐wide emissions 44% higher during the drier year due to an earlier onset and longer duration of the high‐emission summer period. Near‐sediment temperature and water‐column depth were the primary predictors of seasonal CH 4 emissions, reflecting temperature controls on methanogenesis and hydrological regulation of ebullition. In contrast, CO 2 flux variability was dominated by diel processes, with wind speed emerging as the main predictor of short‐term emissions, while water depth and surface temperature regulated seasonal variability. For both gases, chlorophyll‐a was an important predictor at multiday timescales. Our results demonstrate that the temporal variability of GHG fluxes from Mediterranean reservoirs is highly sensitive to hydrologically mediated changes in lake water levels, particularly for methane. Under climate change, GHG emissions could increase significantly in Mediterranean regions, and potentially in other seasonally dry regions worldwide, as a result of projected trends towards stronger eutrophication and increases in drought frequency and duration. Our study underscores the value of long‐term, high‐frequency observations to improve emission estimates and to better represent reservoir processes in regional and global carbon cycle assessments.

Microbial communities and pharmaceutical contaminants in the water-soil–plant continuum of sugarcane crops irrigated with contaminated waters from the Cauca River Valley, Colombia - Juan Ceballos-Castillo; Rodrigo A. Echeverry-Gallego; Diana Martínez-Pachón; Alejandro Moncayo-Lasso; Javier Vanegas (Environmental Science and Pollution Research, 2026)
“Agricultural irrigation with contaminated water poses a major risk to food security and public health. This study examined contaminant transfer across the water–soil–plant continuum in sugarcane crops irrigated with water from the Cauca River, Colombia. Microbial community composition was characterized using 16S rRNA gene sequencing, while pharmaceutical active compounds (PhACs) in irrigation water and sugarcane plants were quantified by UHPLC–MS/MS. Microbial analyses revealed a potential biological pathway of microorganisms from water and soil into plant endophytic tissues. Bacterial diversity decreased markedly, from more than 400 genera identified in water and soil to only 64 genera detected within endophytic tissues. Nine potentially pathogenic genera-including Escherichia–Shigella , Pseudomonas , and Bacillus - were found across all matrices, suggesting microbial internalization. Bioinformatic predictions indicated the presence of genes associated with virulence traits (e.g., antimicrobial resistance and biofilm formation) as well as beneficial functions such as nitrogen fixation and phosphate solubilization. In parallel, high concentrations of PhACs were detected in irrigation water, including valsartan (up to 1309 ng L⁻ 1 ) and diclofenac (up to 969 ng L⁻ 1 ), whereas none or only low concentration detected in sugarcane tissues. Overall, the primary risk to human health appears to stem not from chemical uptake but from microbial infiltration shaped by environmental pressures. Therefore, managing plant-associated microbiomes is essential to mitigate health risks while harnessing biotechnological potential for sustainable agriculture.”

Origin and pre-eruptive conditions of felsic volcanic rocks from the Pinturas River, Patagonia: representatives of the last volcanic episodes of the Jurassic Chon Aike SLIP - Claudia Beatriz Zaffarana; César Rodrigo Navarrete; Gloria Gallastegui; Natalia Hauser; Darío Orts; Víctor Ruiz González; Rodrigo Javier Suárez (International Geology Review, 2026)

Valorization of native grape pomace through vesicular nanocarriers for the enhanced delivery of high-value natural bioactive compounds in green cosmeceutical applications - Francisco Javier Leyva-Jiménez; Silvia Rodrigo-Gallego; Ines Castangia; Francisca Rodrigues; Maria Letizia Manca; Maria Elena Alañón (Sustainable Chemistry and Pharmacy, 2026)

Tableting of nanoparticle-based formulations for oral delivery: Enhancing biopharmaceutical performance - Sofía Peñaloza; Rodrigo Rozas; Andrés Núñez-Salinas; Rodrigo Pérez; Andrea Ortiz; Javier Morales; Francisco Arriagada (DARU Journal of Pharmaceutical Sciences, 2026)

Metagenomic analysis of the tomato microbiome in Colombia reveals bacterial diversity, potential pathogens, and resistance determinants - Yefferson Enciso-Rodríguez; Rodrigo Echeverry-Gallego; Diego C. Franco; Jimena Sánchez; Alejandro Moncayo-Lasso; Diana Martínez-Pachón; Javier Vanegas (Food Research International, 2026)

Spatial richness patterns of large pelagic fishes in the Eastern Pacific Ocean - Aura Buenfil-Ávila; Sofia Ortega-García; Héctor Villalobos; Javier Nori; Ulianov Jakes-Cota; Rodrigo Moncayo-Estrada; Gabriel Reygondeau (Marine Environmental Research, 2026)

Livestock production systems shape alpha and beta diversity of small mammal assemblages - Rodrigo Javier Alonso; Rosario Lovera; Melanie Ruiz; Malena Rospide; Martin Neyen Lammen; Daniela Paula Montes de Oca; Juliana Sánchez; Regino Cavia (Agriculture, Ecosystems & Environment, 2026)

Peptide and osteological evidence for sex bias in megalithic tombs of La Lora region, Northern Iberia - Angélica Santa Cruz; Teresa Fernández-Crespo; Ana María Casas-Ferreira; Miguel del Nogal Sánchez; José Luis Pérez Pavón; Rodrigo Villalobos García; Miguel Moreno Gallo; Javier Basconcillos-Arce; Germán Delibes de Castro (Archaeological and Anthropological Sciences, 2026)
Burial patterns of ancient communities based on the analysis of human remains are difficult to define. In this regard, the existence of a sex bias in megalithic tombs of western Europe remains unclear. Sex estimation using standard osteological methodologies based on dimorphic features is a complex task in commingled and fragmentary human skeletal assemblages, as those found in megalithic burials usually are. Fortunately, advances in molecular archaeological research have made it possible to accurately estimate karyotypic sex. In this work, karyotypic sex is estimated from 85 individuals of all age groups from the megalithic burials of La Lora region (Burgos, Spain) through amelogenin peptides from dental enamel to compare with and extend osteological sex estimations and to calculate sex ratios in these assemblages. The results suggest an overall over-representation of males, in agreement with previous osteological data, despite inter-site variability. Some diachronic variations in the sex ratio have also been detected, which may nuance the trend. Specifically, an increase in the ratio of males at the end of the 4th millennium cal. BC, which may be linked to diachronic changes related to social organisation. The results also suggest that sex-related selective burial in non-adult groups would be less restrictive, as more juvenile females were identified, which could point towards patterns of adult female exogamy.

High-resolution modeling of local-scale currents using machine learning and artificial intelligence: application to Santander Bay - Mirko Rupani; Ana J. Abascal; Rodrigo Manzanas; Javier García-Alba; Andrés García (Frontiers in Marine Science, 2026)
High-resolution hydrodynamic data are essential for coastal and estuarine management. However, traditional downscaling methods based on numerical modeling remain computationally expensive, limiting their applicability for long-term hindcasts and operational forecasting systems. This study evaluates the use of machine learning for the reconstruction of sea surface height and surface currents in a semi-enclosed estuary, using Santander Bay as a case study. Three techniques spanning increasing model complexity are analyzed: K-nearest neighbors, Adaptive Boosting, and long short-term memory networks. The models are trained to emulate high-resolution hydrodynamic-model outputs using a comprehensive set of tidal, meteorological, and fluvial forcings. Performance is assessed through spatial validation, cluster-based analysis, representative-point time series, and independent comparison against in-situ observations. Results show that all techniques successfully reproduce the main hydrodynamic patterns, with accuracy increasing with model complexity. Long short-term memory networks achieve the highest skill in tidally energetic regions, while Adaptive Boosting provides more stable performance in low-energy and shoreline areas. Computational cost analysis demonstrates that all machine-learning approaches achieve speedups of several orders of magnitude relative to numerical modelling, with inference costs that are negligible at both point and domain scales. These findings demonstrate the potential of machine learning as a computationally efficient approach for high-resolution modelling of coastal hydrodynamics, with important implications for operational forecasting and coastal management applications.

Long-term dynamics of groundwater levels under rice-based irrigation systems in South-East Kazakhstan - Dinara B. Barmakova; Javier Rodrigo-Ilarri; Ilan I. Shakibayev; María-Elena Rodrigo-Clavero; Zhaiyk Yerikuly; Vyacheslav A. Zavaley (Paddy and Water Environment, 2026)
Kazakhstan, located predominantly in an arid climatic zone, relies heavily on irrigation to sustain paddy farming and ensure food security. However, prolonged irrigation practices have substantially altered the groundwater regime, affecting groundwater levels, recharge-discharge patterns and the water-salt balance of soils. These transformations, often difficult to reverse, impact both irrigated lands and adjacent areas, compromising land productivity and the sustainability of rice farming systems. Groundwater dynamics in these areas result from the interplay between natural factors (such as climatic variability, natural drainage and sediment filtration properties) and anthropogenic drivers, including the types and condition of irrigation systems, crop patterns, irrigation scheduling and water management practices. In recent years, climate change, water scarcity, and the degradation of irrigation infrastructure have intensified these processes. This study, based on long-term hydrogeological monitoring data, analyses groundwater regime changes in rice-based irrigation systems of South-East Kazakhstan and evaluates their implications for soil conditions and agricultural productivity. The results reveal heterogeneous spatial and temporal patterns: declining groundwater levels in some areas have alleviated waterlogging and improved soil conditions, while other zones still suffer from waterlogging and soil salinization, limiting crop yields. The identified patterns provide a robust basis for designing adaptive irrigation and groundwater management strategies to enhance the sustainability and resilience of rice farming systems under increasing climatic and hydrological challenges.

The progression of triple-negative breast cancer is linked to a gradual decrease of the BK channel in the plasma membrane and an increase in intracellular structures - Rodrigo Zamora-Cárdenas; Ana Laura López-Serrano; Tania Ferrer; Javier Alamilla; Aldo A. Rodríguez-Menchaca; Eloy G. Moreno-Galindo; Ricardo A. Navarro-Polanco (Pflügers Archiv - European Journal of Physiology, 2026)

Hydrodynamic modeling and risk assessment of surge events in the Kazakh sector of the Caspian Sea - Aizat G. Yeltay; Serik B. Sairov; Tursyn A. Tillakarim; Nurgalym T. Serikbay; Dias B. Rakishev; María-Elena Rodrigo-Clavero; Javier Rodrigo-Ilarri (Natural Hazards, 2026)

Influence of Anatomical Definition and Substrate Condition on Simulations of Atrial Arrhythmias - Javier Barrios-Álvarez de Arcaya; María Termenón-Rivas; Giada S. Romitti; Alejandro Liberos; Miguel Rodrigo (Annals of Biomedical Engineering, 2026)

Chemical arsenal of sea anemones: antifouling effects on bryozoan larvae and interspecific interactions - Javier Pinochet; Rodrigo Placencia; Antonio Brante; Marcelo E. Lagos (Biofouling, 2026)

Cultivar plasticity in temperate fruit trees across the Mediterranean region: Different combinations of chill and heat lead to dormancy release - Alvaro Delgado; David Ruiz; Javier Rodrigo; Eike Luedeling; Eduardo Fernandez; Hajar Mojahid; Brenda I. Guerrero; M. Engracia Guerra; Nestor Santolaria; Patricia Irisarri; Jose A. Egea; Lars Caspersen; et al. (European Journal of Agronomy, 2026)

Vegetation type and climate determine temperature thresholds of soil respiration across drylands - María Almagro; Ana Rey; Rosa M. Inclán; Josep Barba; Rodrigo Vargas; Arnaud Carrara; José M. Grünzweig; Marcelo Sternberg; Yiftach Talmon; Rebecca L. McCulley; Sara Marañón-Jiménez; Penélope Serrano-Ortiz; et al. (Soil Biology and Biochemistry, 2025)

Long-term compositional and eruptive transitions in an early Miocene volcanic system, Central Chile (33°S) - Ítalo Payacán; Martín Meyer; Javier Reyes; Lorenzo Tavazzani; Rodrigo Quiroga; Javiera Muñoz; Francisco Gutiérrez; Sebastián Santibáñez (Journal of Volcanology and Geothermal Research, 2025)

Water security in a semiarid environment: An approach to assess costs and benefits of high-Andean nature-based solutions - Sebastián Vicuña; Carlos A. Bonilla; Aurora Gaxiola; Javier I. Rivera; Diego Gonzalez; Sebastián Aedo-Quililongo; Alejandra Vega; Pablo Pastén; Eduardo Bustos; Oscar Melo; Rodrigo Labatut; Juan Pablo Herane; et al. (Ecosystem Services, 2025)

Contrasting responses to climate change – predicting bloom of major temperate fruit tree species in the Mediterranean region and Central Europe - Lars Caspersen; Katja Schiffers; Antonio Picornell; Jose A. Egea; Alvaro Delgado; Adnane El Yaacoubi; Haïfa Benmoussa; Javier Rodrigo; Erica Fadón; Mehdi Ben Mimoun; Mohamed Ghrab; Ossama Kodad; et al. (Agricultural and Forest Meteorology, 2025)

Proximity to Natural Habitat Is Not Consistently Associated With Pollination Services in Tropical Smallholder Farms: A Systematic Review and Meta‐Analysis - Ennia Bosshard; Mark E. Harrison; Frank van Veen; Chris J. Kettle; Nagaraja Badenahally Chikkarangappa; John E. Banks; Parthiba Basu; Quebin Bosbely Casiá‐Ajché; Bo Dalsgaard; Aditi Dutta; Eunice Enríquez; Natalia Escobedo‐Kenefic; et al. (Ecology Letters, 2025)
Proximity to natural habitat is known to enhance pollination services in large‐scale agriculture, but it remains unclear whether this holds in tropical smallholder farms. These systems are embedded in ecologically complex landscapes, central to global food security, and depend heavily on biodiversity‐derived ecosystem services. We conducted a systematic review and meta‐analysis of 35 studies assessing the relationship between distance to natural habitat and pollinator abundance, species richness, and crop fruit set in tropical smallholder farms. We found no consistent patterns in pollinator abundance and crop fruit set with increasing distance, with relationships highly variable across studies. Similarly variable, yet slightly negative, was the relationship between distance and pollinator species richness. Our findings suggest limited support for the ‘proximity to natural habitat’ hypothesis in tropical smallholder farms, indicating that the inherent complexity of these landscapes may buffer negative effects of distance on pollination. This underscores the importance of maintaining and restoring landscape complexity to sustain biodiversity and ecosystem services such as crop pollination. We also highlight the need for greater methodological consistency and publicly available raw data in future studies to strengthen the evidence base and support management strategies for safeguarding pollination services in tropical smallholder farms.

Neogene to Quaternary spatio-temporal evolution of volcanism in the Lazufre Volcanic Area, Southern Central Volcanic Zone: insights from tectonic and magmatic processes - Matias Arriagada; Rodrigo González T.; Gabriel Ureta; Idir Bascuñán; Ángelo Vallejos; Javier Bahamondes; Joaquín Cortés-Aranda; Gonzalo Moreno (Bulletin of Volcanology, 2025)

Assessment of light environment conditions for reconstruction of multispectral images by conditional adversarial networks - Tito Arevalo-Ramirez; Oswaldo Menéndez; Juan Villacrés; Javier Guevara; Robert Guamán-Rivera; Rodrigo Demarco; Fernando Auat Cheein (Biosystems Engineering, 2025)

Beyond climate: Anthropogenic pressures reshape vampire bat distributions across the neotropics - Diana M. Girón-Juárez; Rusby G. Contreras-Díaz; Rodrigo A. Medellín; Octavio Rojas-Soto; Sergio Díaz-Martínez; Javier Nori; Gerardo Martín; Luis Osorio-Olvera (Biological Conservation, 2025)

Patterns of circulating cytokines after 2 types of exercise in active type-1 diabetic patients - María Herranz-López; Rodrigo Martín-San Agustín; Mariló Olivares-Vicente; Laura Pardines-Oltra; Alba Cuerda Del Pino; Jorge Bondia; Paolo Rossetti; F. Javier Ampudia-Blasco; Enrique Roche (Journal of Physiology and Biochemistry, 2025)
Aerobic training (beneficial for type 1 diabetes mellitus (T1DM) patients) could result boring, leading to inactivity or suboptimal performance. Therefore, High-Intensity Interval Training (HIIT) could be an appealing alternative. The present study aimed to compare modulation of certain inflammatory cytokines in T1DM participants performing aerobic vs. HIIT routines. We recruited 26 T1DM male subjects: ages 18–40, T1DM ≥ 2 years, glycated hemoglobin < 8.5%, stable insulin regimen for 6 months, minimum 90 min weekly physical activity and completion of International Physical Activity Questionnaire (IPAQ). IPAQ:2 corresponds to moderate activity and IPAQ:3 to intense physical activity. Participants performed a single aerobic or HIIT session separated by at least 72 h. Blood plasma samples were collected 20 min before and after each session. Cytokines were measured using LUMINEX technique. After aerobic exercise, pro-inflammatory cytokines interleukin (IL)-1β, IL-6, IL-7, IL-8, IL-17 A, tumor necrosis factor-α (TNF-α) and interferon-γ (IFN-γ) showed no significant differences in participants (IPAQ:2 and 3). Only anti-inflammatory cytokine IL-2 increased significantly in IPAQ:3 participants. Compared to pre-exercise, post-exercise HIIT situation presented a similar pattern. The 4 participants (IPAQ:3) that voluntarily followed a 12-week HIIT routine, showed significant increases in IL-7, IL-8, and TNF- α, and the detection of the anti-inflammatory cytokine IL-22. Altogether, these results suggest that HIIT favors the presence of some pro-inflammatory cytokines. The anti-inflammatory action of certain cytokines, such as IL-22, should be considered for a possible compensatory action. Nevertheless, programs of interval exercises at moderate intensity could be at the moment a safe option for T1DM patients.

Between oceans: stepping-stone dispersal and the Pacific-to-Atlantic expansion of Chinook salmon across Patagonia - Carla Riva-Rossi; Javier Ciancio; Daniel Gomez-Uchida; Miguel Pascual; Rodrigo Clarke; Pamela Quiroga; Cecilia Di Prinzio; Carolina Lázari; John Carlos Garza (Frontiers in Marine Science, 2025)
Introduction Biological invasions are major drivers of biodiversity loss worldwide, and salmonid introductions are among the most transformative events in the Southern Hemisphere. The rapid, large-scale expansion of Chinook salmon ( Oncorhynchus tshawytscha ) across South America, driven by high migratory capacity, straying rates, and genetic adaptability, constitutes an unprecedented salmonid invasion. In Patagonia, this spread is accelerating, yet the mechanisms enabling long-distance marine dispersal, successful freshwater colonization, and secondary expansion remain poorly understood. A recently established population in the De las Vueltas River (DLVR), an upper tributary of the Santa Cruz River in Argentine Patagonia, was examined as a key node in the invasion network connecting Pacific-origin populations with new Atlantic Ocean basins. Methods Two high-resolution SNP panels (96 and 172 loci) were used to investigate the genetic origins and colonization dynamics of the DLVR population. Tissue samples from 70 fish collected in 2014–2015 were genotyped and compared with North American source lineages to infer ancestral origins, and with Pacific and Atlantic naturalized populations to reconstruct recent invasion pathways. Discriminant analysis of principal components (DAPC), genetic mixture modeling, and Bayesian assignment implemented in the R package rubias were performed. Simulations were used to harmonize SNP data across panels and to improve assignment accuracy. Results The genetic roots of the DLVR population were traced to stocks from the Lower Columbia River fall and spring runs and the Willamette River spring run. Strong genetic affinities were detected with naturalized populations from Chile’s Aysén Region, particularly the Cobarde and Vargas Rivers, while smaller contributions from Santa Cruz River populations were inferred. These findings indicate colonization through long-distance oceanic or trans-Andean dispersal, followed by secondary expansion within the Santa Cruz basin. Discussion The role of ocean connectivity, stepping-stone habitats, and leading-edge dispersal in enabling the rapid eastward spread of Chinook salmon is highlighted by these results. The Santa Cruz River basin is identified as a critical invasion hub, concentrating propagules from multiple lineages and promoting multi-step dispersal into new Atlantic Ocean basins. These insights emphasize the need to incorporate riverine connectivity and invasion hubs into management strategies to mitigate the ecological and evolutionary impacts of Chinook salmon in South America.

Evolution of debris cones with TLS (2009–2024) and development of predictive techniques with functional data - José Juan de Sanjosé-Blasco; Mariló López; Enrique Serrano; Estrella Alonso; Javier Rodrigo (Landslides, 2025)
This study aims to analyse the dynamic of two debris cones (Cone A and Cone B) in Picos de Europa in the northern Iberian Peninsula. Terrestrial laser scanning (TLS) technology was used for their continuous assessment every August for 16 years (2009–2024). The statistical predictive value of position ( Z ) in 2024 was calculated for the same planimetric position ( X , Y ) throughout all the profiles of maximum slopes of the digital elevation model (DEM) of 2009. To do so, we interpolated the actual field data from 2009 to 2023 and used them to form a sample of curves, which are interpreted as the realization of a functional random variable that can be predicted using statistical techniques. The predictive curve obtained was compared with the 2024 field data. The results of both coordinates ( Z ), the actual field data, and the statistical data are coherent within the margin of error of the data collection. The observations and calculations of the two debris cones were treated independently, but both showed the same behaviour. In this way, the present study demonstrates the goodness of some statistical techniques for the functional analysis of data that allow predicting displacement curves by adjusting the model to the sample of movement curves from previous years.

Reaction of Minimal Streamflow to Natural Factors in the Context of Climate Uncertainty - Lyazzat Birimbayeva; Lyazzat Makhmudova; Sayat Alimkulov; Aisulu Tursunova; Dimitris Tigkas; Nurlan Abayev; Aigerim Dostayeva; Zhomart Birimbayev; Oirat Alzhanov; María-Elena Rodrigo-Clavero; Javier Rodrigo-Ilarri (Water Resources Management, 2025)
This study analyzes long-term changes in minimal streamflow in the Zhaiyk-Caspian Water Management Basin (WMB), Western Kazakhstan, under climate variability. Using extensive hydrometeorological datasets (monthly discharge and daily meteorological records) from 1940 to 2021, the research assesses trends in low-flow characteristics across 18 hydrological posts. The analysis distinguishes two climatic periods: climate stabilization (pre-1973) and climate change (1974–2021). The methodology integrates hydrological and statistical analyses, including minimal monthly discharges, low-flow durations, soil freezing depths, and thaw frequencies. Findings reveal a widespread increase in winter low flows—up to 5.2 times—due to reduced frost depths and more frequent thaw events, enhancing groundwater contributions. Conversely, summer-autumn flows declined in several rivers, with drying trends linked to rising air temperatures and precipitation deficits. This study offers a novel, regionally adapted methodology for characterizing minimal streamflow under climate change, providing critical insights for hydrological drought assessment and water resource planning in arid and semi-arid environments.

Body mass index and prognosis of infective endocarditis - Raquel Frías-García; Patricia Muñoz García; Marina Machado Vilchez; Gregorio Cuerpo Caballero; Raquel Rodríguez-García; M Ángeles Rodríguez-Esteban; M Carmen Fariñas-Álvarez; José M. Miró Meda; Andrea Gutiérrez Villanueva; Guillermo Ojeda-Burgos; Ane Josune Goikoetxea-Agirre; Marina Bernal Palacios; et al. (Infectious Diseases, 2025)

Diversity and composition of seed-carrying ant assemblages in the Monte desert: a regional assessment of the effects of grazing - Maria Florencia Miretti; Rodrigo G. Pol; Carolina I. Paris; Vanina Elizalde Capellino; Ramón Alberto Sosa; Javier Lopez de Casenave (Journal of Insect Conservation, 2025)

Large cutting tools from SHK (Bed II, Olduvai Gorge, Tanzania): a techno-functional approach - Javier Duque-Martínez; Fernando Diez-Martín; Cristina Fraile-Márquez; Sara de Francisco; Enrique Baquedano; Audax Mabulla; Manuel Domínguez-Rodrigo (Archaeological and Anthropological Sciences, 2025)

Impact of a Novel Aquatic-Based Strength Program on Body Composition, Strength, and Quality of Life in Older Women: a 16-Week Randomized Controlled Trial - Alvaro Juesas; Carlos Babiloni-Lopez; Javier Gene-Morales; Pablo Jiménez-Martínez; Rodrigo Ramirez-Campillo; Juan C. Colado (Journal of Science in Sport and Exercise, 2025)
Purpose This study aimed to compare the effects of water- versus land-based resistance training on body composition (fat and muscle mass), strength (isometric and isokinetic), and health-related quality of life in older women. Methods Ninety-three apparently healthy volunteers (age: 68.91 ± 5.05 years) participated in this prospective randomized controlled trial and were divided into three groups with a block-design randomization sequence: (i) water-based training (WG) using drag devices at a fast-paced execution, (ii) land-based training (LG) using tornado devices at a moderate-paced execution, and (iii) control group (CG) with no training. The training program lasted 16 weeks, with two weekly sessions, each including three upper-limb and three lower-limb exercises. Both groups progressively increased intensity (rating of perceived exertion) and volume (sets) throughout the program. Each set lasted 40 s, with LG performing 10 repetitions (2 s concentric, 2 s eccentric) and WG performing as many repetitions as possible. Results Significant group × time effects were found for body fat ( P = 0.016, η p 2 = 0.13), upper-limb muscle mass ( P = 0.027, η p 2 = 0.12), all isometric strength tests ( P < 0.001, η p 2 = 0.45–0.57), and isokinetic knee extension at 60º/s and 180º/s ( P = 0.001–0.013, η p 2 = 0.15–0.26). No significant differences were found between LG and WG in most variables ( P > 0.05). The WG significantly improved isometric vertical row ( d = 1.47), isokinetic knee extension ( d = 0.41–1.11), physical function ( d = 0.44), and body pain ( d = 0.50), while the LG did not. Conversely, only the LG significantly reduced body fat ( d = 0.24). Conclusion Although both training programs show similar results, power training in water significantly improves strength parameters and health-related quality of life, while moderate-paced resistance training on land effectively reduces body fat.

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Black soldier frass valorization into low-cost residual biofertilizer conversion process and its effectiveness in foliar and soil applications - Naysha Yamelit Meza Elguera; Dana Lucia Ramos Zorrilla; Javier Rodrigo Heredia Sucari; Humberto Jose Stretz Chavez; Abdel Alejandro Portocarrero Banda; Ingrind Mirna Diaz Vento; Hugo Guillermo Jiménez Pacheco (Bioresource Technology Reports, 2025)

Bird–window collisions: A comprehensive dataset for the Neotropical region - Augusto João Piratelli; Bianca Costa Ribeiro; Wesley Dáttilo; Luis‐Bernardo Vázquez; Anelisa Ferreira de Almeida Magalhães; Edna Maria Gomes Cavalcante; Eric Silva; Giovanna Viana Cruz; Gisele Regina Ruy; Juliana Laurito Summa; Júlia Milan; Leila Pedrosa; et al. (Ecology, 2025)
Our primary objective was to compile a comprehensive dataset on bird–window collisions throughout the Neotropical region, including both published and unpublished sources. On May 12, 2020, we extensively disseminated invitations to provide data via email and social media platforms. By providing a template worksheet, we required standardized information from collaborators to complete and register their data. To better understand how these data were acquired (e.g., incidental observations and systematic procedures), we sent out a survey to all collaborators. We established rigorous validation criteria for data inclusion and conducted thorough curation procedures to ensure accuracy. After the filtering process, we compiled a total of 4103 bird–window collision reports. These came from 11 Neotropical countries, dating from 1946 to 2020, and revealing distinct regional patterns and potential seasonal patterns. The five most frequent orders were Passeriformes (2451), Columbiformes (520), Apodiformes (377), Psittaciformes (202), and Piciformes (186). Data on bird–window collisions were collected through a local specific systematic protocol (1419), by chance (1252), by government agencies (742), and by other approaches (632), while a few reports were collected by unknown procedures (58). The volume of records across months in our dataset suggests that there may be temporal patterns, with peaks: the first one in March–April and the second one in October–November, which seem to align with the major migration and reproduction seasons. This dataset represents the first comprehensive effort in the Neotropical region focused on bird–window collision data, providing valuable insights for further scientific advancements and conservation policies. The data are free from copyright or proprietary restrictions. Please cite this data paper when using the data in publications or scientific presentations.

Octyl levulinate biolubricant production from levulinic acid esterification over ion exchange resins: Role of morphology and reaction thermodynamics - Jordi H. Badia; Rodrigo Soto; Carles Fité; Javier Tejero; Eliana Ramírez (Chemical Engineering Journal, 2025)

Unveiling autarchic photo-thermal capabilities of morphology-tailored SnO2 nanostructures for boosting arsenic photo-oxidation - Maibelin Rosales; Raynald Gauvin; Rodrigo Espinoza-González; Senentxu Lanceros-Méndez; Roberto Fernández de Luis; Javier Vicente; Nicolas Brodusch; Stéphanie Bessette; Barbara Rodríguez; Humberto Estay; Andreina García (Journal of Environmental Chemical Engineering, 2025)

Distance From Nest and Climate Explain Geographical Trends of Harvester Ant's Food Resource Use: A Multi‐Species Approach - Diego Anjos; Pedro Luna; Kleber Del‐Claro; Rodrigo G. Pol; Javier Lopez de Casenave; Helena Maura Torezan‐Silingardi; Martha L. Baena; Florencia Baudino; Judie Bronstein; Melissa Burt; Eduardo Calixto; Ana Laura Cao; et al. (Journal of Biogeography, 2025)
Main Animals not only forage for abundant and nearby resources, but their diets can also be influenced by abiotic and geographic factors. This often results in non‐random interactions among species. We investigate how seed density, distance from nest, abiotic (e.g., climate stability, temperature, precipitation) and geographic factors (e.g., latitude, elevation and continental hemisphere) influence the removal of food items (i.e., seeds and dead arthropods) by Pogonomyrmex species. Location South and North America, from Patagonia to the Rocky Mountains. Taxon Genus Pogonomyrmex (Formicidae: Hymenoptera). Methods Conducting standardised experiments, we performed a seed removal experiment and an assessment of the items retrieved by ant workers of 160 nests from eight Pogonomyrmex spp. at 16 sites extending the American continent. Results Pogonomyrmex ants native to North America removed more seeds than their South American counterpart. In general, results align with optimal foraging theory, indicating a higher probability of seed removal near ant nests. High climate stability correlated with lower seed predation rates, emphasising seed consumption's significance in historically arid environments. Increased precipitation and temperature led to reduced removal of food resources, suggesting reduced water availability and lower mean temperatures increases the consumption of seeds by harvester ants. Conclusions Overall, Pogonomyrmex ants' food resource use is influenced by a combination of factors such as region, distance from the nest and climate. This study underscores harvester ants' potential impact on plant distribution over large spatial scales consuming seeds from the immediate proximity of their nest and preventing establishment.

From spores to gametes: A sexual life cycle in a symbiotic Trebouxia microalga - Ayelén Gazquez; César Daniel Bordenave; Javier Montero-Pau; Marta Pérez-Rodrigo; Francisco Marco; Fernando Martínez-Alberola; Lucia Muggia; Eva Barreno; Pedro Carrasco (Algal Research, 2024)

FreshLanDiv : A Global Database of Freshwater Biodiversity Across Different Land Uses - Minghua Shen; Roel van Klink; Alban Sagouis; Danielle K. Petsch; Deborah Atieno Abong'o; Janne Alahuhta; Salman Abdo Al‐Shami; Laura Cecilia Armendáriz; Mi‐Jung Bae; Tiago Octavio Begot; Jerome Belliard; Jonathan Peter Benstead; et al. (Global Ecology and Biogeography, 2024)
Motivation Freshwater ecosystems have been heavily impacted by land‐use changes, but data syntheses on these impacts are still limited. Here, we compiled a global database encompassing 241 studies with species abundance data (from multiple biological groups and geographic locations) across sites with different land‐use categories. This compilation will be useful for addressing questions regarding land‐use change and its impact on freshwater biodiversity. Main Types of Variables Contained The database includes metadata of each study, sites location, sample methods, sample time, land‐use category and abundance of each taxon. Spatial Location and Grain The database contains data from across the globe, with 85% of the sites having well‐defined geographical coordinates. Major Taxa and Level of Measurement The database covers all major freshwater biological groups including algae, macrophytes, zooplankton, macroinvertebrates, fish and amphibians.

Refining the chronology of Middle/Late Pleistocene fossil assemblages in the Argentine Pampas - Jose Luis Prado; Mathieu Duval; Martina Demuro; Francisco Javier Santos-Arévalo; María Teresa Alberdi; Rodrigo L. Tomassini; Claudia I. Montalvo; Ricardo Bonini; Cristian M. Favier-Dubois; Sallie Burrough; Szilvia Bajkan; Germán M. Gasparini; et al. (Quaternary Science Reviews, 2024)

On time scales and “synchronic” variability in the archaeology of human origins: short-term technological variations at SHK (Olduvai Gorge, Tanzania) - Fernando Diez-Martín; Cristina Fraile-Márquez; Javier Duque-Martínez; Policarpo Sánchez-Yustos; Sara de Francisco; Enrique Baquedano; Audax Mabulla; Manuel Domínguez-Rodrigo (Archaeological and Anthropological Sciences, 2024)

Is the change deforestation? Using time-series analysis of satellite data to disentangle deforestation from other forest degradation causes - Ignacio Fuentes; Javier Lopatin; Mauricio Galleguillos; Andrés Ceballos-Comisso; Susana Eyheramendy; Rodrigo Carrasco (Remote Sensing Applications: Society and Environment, 2024)

Acoustic detection of the effects of prolonged fasting on newly hatched broiler chickens - Gerardo José Ginovart-Panisello; Ignasi Iriondo; Tesa Panisello Monjo; Silvia Riva; Rodrigo Garcia; Javier Valls; Rosa Ma Alsina-Pagès (Computers and Electronics in Agriculture, 2024)

Lizard host abundances and climatic factors explain phylogenetic diversity and prevalence of blood parasites on an oceanic island - Rodrigo Megía‐Palma; Gemma Palomar; Javier Martínez; Bernardo Antunes; Katarzyna Dudek; Anamarija Žagar; Nina Serén; Miguel A. Carretero; Wiesław Babik; Santiago Merino (Molecular Ecology, 2024)
Host abundance might favour the maintenance of a high phylogenetic diversity of some parasites via rapid transmission rates. Blood parasites of insular lizards represent a good model to test this hypothesis because these parasites can be particularly prevalent in islands and host lizards highly abundant. We applied deep amplicon sequencing and analysed environmental predictors of blood parasite prevalence and phylogenetic diversity in the endemic lizard Gallotia galloti across 24 localities on Tenerife, an island in the Canary archipelago that has experienced increasing warming and drought in recent years. Parasite prevalence assessed by microscopy was over 94%, and a higher proportion of infected lizards was found in warmer and drier locations. A total of 33 different 18s rRNA parasite haplotypes were identified, and the phylogenetic analyses indicated that they belong to two genera of Adeleorina (Apicomplexa: Coccidia), with Karyolysus as the dominant genus. The most important predictor of between‐locality variation in parasite phylogenetic diversity was the abundance of lizard hosts. We conclude that a combination of climatic and host demographic factors associated with an insular syndrome may be favouring a rapid transmission of blood parasites among lizards on Tenerife, which may favour the maintenance of a high phylogenetic diversity of parasites.

How does urbanization affect the fauna of the largest urban forest in Mexico? - Omar Ávalos-Hernández; Marysol Trujano-Ortega; Rubén Ortega-Álvarez; Rodrigo G. Martínez-Fuentes; Rafael Calderón-Parra; Fernando García-Luna; Laura Ramírez-Vieyra; Jesús Tapia-González; Javier Vega-Rivas; Jorge Villagómez-Guijón; Antonio Valdenegro-Brito; Uri O. García-Vázquez (Urban Forestry & Urban Greening, 2024)

Seasonal changes in color patches and parasite load of male torquate lizards (Sceloporus torquatus) - Jimena Rivera-Rea; Juan Carlos González-Morales; Rodrigo Megía-Palma; Elizabeth Bastiaans; Erendira Quintana; Javier Manjarrez (Behavioral Ecology and Sociobiology, 2024)

Correction to: Role of Toll-like receptor 2 and 4 signaling pathways on the inflammatory response to resistance training in elderly subjects - Paula Rodriguez-Miguelez; Rodrigo Fernandez-Gonzalo; Mar Almar; Yubisay Mejías; Ana Rivas; José A. de Paz; María J. Cuevas; Javier González-Gallego (GeroScience, 2023)

Indolealkylamines in the venom of the scorpion Thorellius intrepidus - Rodrigo Ibarra-Vega; Juana María Jiménez-Vargas; Armando Pineda-Contreras; Francisco Javier Martínez-Martínez; Carlos Eduardo Barajas-Saucedo; Héctor García-Ortega; Nancy E. Magaña-Vergara; Lourival D. Possani; Gerardo Corzo; Mario Alberto Gaitan-Hinojosa; Oscar Fernando Vázquez-Vuelvas; Fernando Zamudio; et al. (Toxicon, 2023)

Deep Learning-Based Time Series Forecasting Models Evaluation for the Forecast of Chlorophyll a and Dissolved Oxygen in the Mar Menor - Francisco Javier López-Andreu; Juan Antonio López-Morales; Zaida Hernández-Guillen; Juan Antonio Carrero-Rodrigo; Marta Sánchez-Alcaraz; Joaquín Francisco Atenza-Juárez; Manuel Erena (Journal of Marine Science and Engineering, 2023)
The Mar Menor is a coastal lagoon of great socio-ecological and environmental value; in recent years, different localized episodes of hypoxia and eutrophication have modified the quality of its waters. The episodes are due to a drop in dissolved oxygen levels below 4 mg/L in some parts of the lagoon and a rise in chlorophyll a to over 1.8 mg/L. Considering that monitoring the Mar Menor and its watershed is essential to understand the environmental dynamics that cause these dramatic episodes, in recent years, efforts have focused on carrying out periodic measurements of different biophysical parameters of the water. Taking advantage of the data collected and the versatility offered by neural networks, this paper evaluates the performance of a dozen advanced neural networks oriented to time series forecasted for the estimation of dissolved oxygen and chlorophyll a parameters. The data used are obtained in the water body by means of sensors carried by a multiparameter oceanographic probe and two agro-climatic stations located near the Mar Menor. For the dissolved oxygen forecast, the models based on the Time2Vec architecture, accompanied by BiLSTM and Transformer, offer an R2 greater than 0.95. In the case of chlorophyll a, three models offer an R2 above 0.92. These metrics are corroborated by forecasting these two parameters for the first time step out of the data set used. Given the satisfactory results obtained, this work is integrated as a new biophysical parameter forecast component in the monitoring platform of the Mar Menor Observatory developed by IMIDA. The results demonstrate that it is feasible to forecast the concentration of chlorophyll a and dissolved oxygen using neural networks specialized in time series forecasts.

The Prados del Cervunal morainic complex: Evidence of a MIS 2 glaciation in the Iberian Central System synchronous to the global LGM - Rosa M. Carrasco; Valentí Turu; Rodrigo L. Soteres; Javier Fernández-Lozano; Theodoros Karampaglidis; Ángel Rodés; Xavier Ros; Nuria Andrés; José Luis Granja-Bruña; Alfonso Muñoz-Martín; José Antonio López-Sáez; Regis Braucher; et al. (Quaternary Science Reviews, 2023)

A conceptual digital twin framework for city logistics - Abdelhadi Belfadel; Sebastian Hörl; Rodrigo Javier Tapia; Dimitra Politaki; Ibad Kureshi; Lorant Tavasszy; Jakob Puchinger (Computers, Environment and Urban Systems, 2023)

The application of the photo-electro-Fenton process in the treatment of wastewater reduces the abundance of genes associated with pathogenicity factors, antibiotic resistance, and metabolism: A metagenomic analysis. - Rodrigo A. Echeverry-Gallego; Paula A. Espinosa-Barrera; Carlos A. Delgado-Vargas; Javier Vanegas; Diana Carolina Clavijo-Buriticá; Diana Martínez-Pachón; Alejandro Moncayo-Lasso (Journal of Environmental Chemical Engineering, 2023)

Association of genetic polymorphisms in detoxifying systems and urinary metal(loid) levels with excess body weight among Spanish children: A proof-of-concept study - Viviana Ramírez; Inmaculada Salcedo-Bellido; Lourdes Rodrigo; Fernando Gil Hernández; Pablo Olmedo; Luis Javier Martínez-González; María Jesús Álvarez-Cubero; Ana Rivas (Science of The Total Environment, 2023)

Robust automatic net damage detection and tracking on real aquaculture environment using computer vision - Julio Labra; Marcos D. Zuniga; Javier Rebolledo; Mohamed A. Ahmed; Rodrigo Carvajal; Nicolás Jara; Gonzalo Carvajal (Aquacultural Engineering, 2023)

Searching for intra-site spatial patterns in the African Early Acheulean: the lowermost archaeo-units at FLK West (Olduvai Gorge, Tanzania) - Fernando Diez-Martín; Lucía Cobo-Sánchez; Cristina Fraile-Márquez; Sara de Francisco; Javier Duque-Martínez; Policarpo Sánchez-Yustos; Enrique Baquedano; Audax Mabulla; Manuel Domínguez-Rodrigo (Archaeological and Anthropological Sciences, 2023)

Agroclimatic requirements and adaptation potential to global warming of Spanish cultivars of sweet cherry (Prunus avium L.) - Erica Fadón; Eduardo Fernandez; Eike Luedeling; Javier Rodrigo (European Journal of Agronomy, 2023)

Unveiling the Role of Dynamic Alternative Splicing Modulation After Infestation with Sea Lice (Caligus rogercresseyi) in Atlantic Salmon - Scarleth Bravo; Francisco Leiva; Javier Moya; Osiel Guzman; Rodrigo Vidal (Marine Biotechnology, 2023)

Apparent differences in agroclimatic requirements for sweet cherry across climatic settings reveal shortcomings in common phenology models - Erica Fadón; Hoa Do; Michael Blanke; Javier Rodrigo; Eike Luedeling (Agricultural and Forest Meteorology, 2023)

Climate change impacts on winter chill in Mediterranean temperate fruit orchards - Eduardo Fernandez; Hajar Mojahid; Erica Fadón; Javier Rodrigo; David Ruiz; Jose A. Egea; Mehdi Ben Mimoun; Ossama Kodad; Adnane El Yaacoubi; Mohamed Ghrab; José Egea; Haïfa Benmoussa; et al. (Regional Environmental Change, 2023)
Temperate trees require low temperatures during winter and subsequent warm conditions in early spring to flower and eventually bear fruit. Many parts of the Mediterranean region feature winters with low and sometimes marginal chill accumulation. To assess historic and future agroclimatic conditions for cultivating temperate trees (including almonds, pistachios, apricots, sweet cherries and apples), we mapped winter chill throughout this important growing region. We used on-site weather records (1974–2020) to calibrate a weather generator and produced data for historic and future scenarios. To broaden our analysis, we spatially interpolated chill for the whole Mediterranean basin. We supplemented our simulation outcomes by collecting expert knowledge (from farmers and researchers) regarding observed climate change impacts on temperate orchards as well as future risks and concerns generated by climate change. Results showed that northern African growing regions have experienced major chill losses, a likely cause of the irregular and delayed bloom highlighted by experts. The same regions, together with southern Europe, may lose up to 30 Chill Portions by 2050 under a moderate warming scenario. For the future, experts foresee increasing risk of spring frost in early-blooming cultivars, exacerbated bloom-related problems and increasing occurrence of heat waves. Our results provide evidence of likely climate change impacts on temperate orchards. Expert knowledge proved instrumental in interpreting the simulation results as well as in orienting climate change adaptation strategies. The results we present are useful for farmers and orchard managers planning new plantings, as well as for researchers and policy makers developing strategies to adapt fruit orchards to the impacts of climate change.

Comprehensive review of natural based hydrogels as an upcoming trend for food packing - Francisco Javier Leyva-Jiménez; Rodrigo Oliver-Simancas; Ines Castangia; Antonio M. Rodríguez-García; M. Elena Alañón (Food Hydrocolloids, 2023)

A new method based on machine learning to forecast fruit yield using spectrometric data: analysis in a fruit supply chain context - Javier E. Gómez-Lagos; Marcela C. González-Araya; Rodrigo Ortega Blu; Luis G. Acosta Espejo (Precision Agriculture, 2023)

Boreal winter stratospheric climatology in EC-EARTH: CMIP6 version - Froila M Palmeiro; Javier García-Serrano; Mario Rodrigo; Marta Abalos; Bo Christiansen; Shuting Yang (Climate Dynamics, 2023)
The performance of the European Consortium Earth-system model (EC-EARTH) in the boreal winter stratosphere is comprehensively assessed for the first time, in particular its version 3.3 that contributes to CMIP6. A 100-year long simulation with prescribed climatological boundary conditions and fixed radiative forcing, representative of present-day climate, is used to evaluate the simulation of the climatological stratospheric circulation and to identify model biases. Results show that EC-EARTH has a large issue with the vertical distribution of stratospheric temperature from the tropics to mid-latitudes, seemingly linked to radiative processes of ozone, leading to a biased warm middle-upper stratosphere. Associated with this model bias, EC-EARTH simulates a stronger polar vortex at upper-stratospheric levels while the Brewer-Dobson circulation at middle/lower levels is weaker than reanalysis. The amplitude of the climatological planetary waves is overall underestimated, but the magnitude of the background wave injection from the troposphere into the stratosphere is overestimated, related to a weaker polar vortex at lower-stratospheric levels and, thus, a less effective wave filtering. This bias in the westerly flow could have a contribution from parameterized waves. The overestimation of background wave driving is maximum in early-winter, and may explain the overestimated frequency of sudden stratospheric warmings at this time, as compared to reanalysis. The spatial distribution of wave injection climatology has revealed a distinctive role of the climatological planetary waves: while large-scale waves (wavenumbers 1–2) dominate the eddy heat flux over the North Pacific, small-scale waves (wavenumbers 3–4) are responsible for the doubled-lobe structure of the eddy heat flux over Eurasia. EC-EARTH properly simulates this climatological feature, although overestimates its amplitude over central Eurasia.

Facing the palimpsest conundrum: an archaeo-stratigraphic approach to the intra-site analysis of SHK Extension (Bed II, Olduvai Gorge, Tanzania) - Cristina Fraile-Márquez; Fernando Diez-Martín; Javier Duque-Martínez; David Uribelarrea; Policarpo Sánchez-Yustos; Sara de Francisco; Enrique Baquedano; Audax Mabulla; Manuel Domínguez-Rodrigo (Archaeological and Anthropological Sciences, 2022)

Two constructed wetlands within a Mediterranean natural park immersed in an agrolandscape reduce most heavy metal water concentrations and dampen the majority of pesticide presence - Maria A. Rodrigo; Eric Puche; Nuria Carabal; Sergio Armenta; Francesc A. Esteve-Turrillas; Javier Jiménez; Fernando Juan (Environmental Science and Pollution Research, 2022)
The water concentrations of 12 heavy and other metals/metalloids were analyzed seasonally along two horizontal-flow constructed wetlands (CWs) (Tancat Mília—TM and Tancat l’Illa—TLI) located within the Mediterranean Albufera de València Natural Park during 2020–2021. A wide-scope screening of pesticides present in waters was also performed. The two CWs were created to improve water quality and increase biodiversity. They currently receive effluent waters from two different tertiary-treatment wastewater plants, and the water flows along the CWs before being discharged into the main lagoon and a smaller lagoon in TM and TLI, respectively. TLI manages to reduce (Mn) or maintain the concentration of most of the studied elements (Zn, Ni, Hg, Cr, Fe Cd, Cu) at the same level as outside (67%). Only Al, Pb, B, and As remain at a higher concentration. TM also reduces Zn and Cu and keeps the concentration of Cr, Cd, and Hg (representing 42%). Al, Pb, B, and As remain at higher concentrations, as in TLI, but Ni, Fe, and Mn are also at higher concentrations. Although both CWs vary in their ability to remove elements, no risks to human health or the environment have been detected due to the low metal concentration in their outlets, all of them (except Hg) below the legal limits for environmental quality in the European Union. With the detection of 71 compounds in water in each CW area (26 herbicides, 26 insecticides, and 19 fungicides in TLI, and 29 herbicides, 23 insecticides, and 19 fungicides in TM), we also provide evidence of the impact of pesticides, which depends on the application method (helicopter, tractor), originated from areas with high agricultural pressure (chiefly rice crops) on systems (mainly TM) created to preserve biodiversity. Nevertheless, both systems provide crucial environmental services in water quality in this agrolandscape.

Underwater Anthropogenic Noise Pollution Assessment in Shallow Waters on the South-Eastern Coast of Spain - Francisco Javier Rodrigo; Jaime Ramis; Jesus Carbajo; Pedro Poveda (Journal of Marine Science and Engineering, 2022)
Anthropogenic noise is a growing threat to marine life due to the incrementation of human activity in the marine environment. In Europe, the Directive 2008/56/EC of the European Parliament and of the Council was published with the aim of establishing a framework for community action in the field of marine environmental policy. The directive introduces underwater acoustic energy, as detailed in Descriptor 11, and stipulates that the member states should set the threshold levels at which a good environmental status can be achieved by means of long-term monitoring campaigns. This research presents the results of a long-term underwater noise monitoring campaign with a duration of three years in the port of Cartagena located on the south-eastern coast of Spain, focusing on the monthly and annual variation patterns of low-frequency continuous noise. The acquired data are classified according to the source of the acoustic noise into shipping, other anthropogenic, and natural noise measurements. These three groups of measurements are processed in order to obtain one-third octave band levels centered at 63 and 125 Hz, as well as the overall bandwidth of unweighted Sound Pressure Level (SPL). The analysis of the measurements shows an increase in the annual average overall band of 4 and 3 dB of the natural and shipping noise, respectively, from 2013 to 2015. This monitoring campaign provides accurate acoustic values to establish threshold levels to achieve good environmental status and recommendations to conduct monitoring programs and regulations to control underwater noise pollution.

Phenological variation in parasite load and inflammatory response in a lizard with an asynchronous reproductive cycle - Jimena Rivera-Rea; J. Carlos González-Morales; Víctor Fajardo; Rodrigo Megía-Palma; Elizabeth Bastiaans; Javier Manjarrez (The Science of Nature, 2022)

Growth estimates of young‐of‐the‐year broadnose sevengill shark, Notorynchus cepedianus , a top predator with poorly calcified vertebrae - Andrés Javier Jaureguizar; Federico Cortés; J. Matias Braccini; Rodrigo Wiff; Andrés C. Milessi (Journal of Fish Biology, 2022)
The broadnose sevengill shark, Notorynchus cepedianus (Péron, 1807), is a large marine top predator in temperate coastal ecosystems. Some aspects of its life history have been determined, but its growth pattern is yet to be fully understood. The authors used a multi‐modelling approach and a sensitivity test to estimate growth parameters from young‐of‐year (YOY) length data collected off San Antonio Cape (SAC), Argentina, a critical habitat in the Southwest Atlantic Coastal Zone (SACZ). The best selected model, a sex‐combined logistic growth model, estimated an asymptotic length ( L ∞ ) of 92.58 cm TL (95% C.I. : 86.48–105.89 cm), a growth coefficient (K) of 0.006818 days −1 (95% C.I. : 0.004948–0.008777) and a size at birth ( L 0 ) of 40.73 cm. The predicted annual growth ( i.e ., L 1 – L 0 ) was 43.2 cm TL. Males had smaller L 0 , higher K and achieved larger sizes after 1 year. The YOY in SAC attained a larger L 1 and grew faster than their Australian and South African wild counterparts. The consistent year‐round presence of YOY in the SAC highlights the importance of this area as a pupping ground and potential nursery for N. cepedianus ; this has direct implications for the allocation of research and management effort for the conservation of this species in the Southwest Atlantic.

Role of the YehD fimbriae in the virulence‐associated properties of enteroaggregative Escherichia coli - Jorge Soria‐Bustos; Waleska Saitz; Abraham Medrano; Cristina Lara‐Ochoa; Zineb Bennis; Valerio Monteiro‐Neto; Camilla Itapary dos Santos; Josias Rodrigues; Rodrigo T. Hernandes; Jorge A. Yáñez; Javier Torres; Fernando Navarro‐García; et al. (Environmental Microbiology, 2022)
Summary The interaction of enteroaggregative Escherichia coli (EAEC) strains with the colonic gut mucosa is characterized by the ability of the bacteria to form robust biofilms, to bind mucin, and induce a local inflammatory response. These events are mediated by a repertoire of five different aggregative adherence fimbriae variants (AAF/I‐V) typically encoded on virulence plasmids. In this study, we report the production in EAEC strains of a new Y eh D f imbriae (YDF), which is encoded by the chromosomal gene cluster yehABCD , also present in most E. coli strains. Immuno‐labelling of EAEC strain 042 with anti‐AAF/II and anti‐YDF antibodies demonstrated the presence of both AAF/II and YDF on the bacterial surface. We investigated the role of YDF in cell adherence, biofilm formation, colonization of spinach leaves, and induction of pro‐inflammatory cytokines release. To this aim, we constructed yehD deletion mutants in different EAEC backgrounds (strains 17‐2, 042, 55989, C1010, 278‐1, J7) each harbouring one of the five AAFs. The effect of the YDF mutation was strain dependent and AAF independent as the lack of YDF had a different impact on the phenotypes manifested by the different EAECs tested. Expression of the yehABCD operon in a E. coli K12 ORN172 showed that YDF is important for biofilm formation but not for adherence to HeLa cells. Lastly, screening of pro‐inflammatory cytokines in supernatants of Caco‐2 cells infected with EAEC strains 042 and J7 and their isogenic Δ yehD mutants showed that these mutants were significantly defective in release of IL‐8 and TNF‐α. This study contributes to the understanding of the complex and diverse mechanisms of adherence of EAEC strains and identifies a new potential target for preventive measures of gastrointestinal illness caused by EAEC and other E. coli pathogroups.

Diel changes in structure and trophic functions of motile benthic invertebrates on coral reefs at Rapa Nui (Easter Island) - Germán Zapata-Hernández; Iván A. Hinojosa; Javier Sellanes; Rodrigo S. Rios; Yves Letourneur (Marine Biology, 2021)

Soil organic carbon monitoring to assess agricultural climate change adaptation practices in Navarre, Spain - Rodrigo Antón; Francisco Javier Arricibita; Alberto Ruiz-Sagaseta; Alberto Enrique; Isabel de Soto; Luis Orcaray; Armelle Zaragüeta; Iñigo Virto (Regional Environmental Change, 2021)

Temporal Gene Expression Signature of Plasma Extracellular Vesicles-MicroRNAs from Post-Smolt Coho Salmon Challenged with Piscirickettsia salmonis - Francisco Leiva; Scarlet Bravo; Killen Ko Garcia; Javier Moya; Osiel Guzman; Rodrigo Vidal (Marine Biotechnology, 2021)

Spatiotemporal Precipitation Estimation from Rain Gauges and Meteorological Radar Using Geostatistics - Eduardo Cassiraga; J. Jaime Gómez-Hernández; Marc Berenguer; Daniel Sempere-Torres; Javier Rodrigo-Ilarri (Mathematical Geosciences, 2021)

Biphasic growth modelling in elasmobranchs based on asymmetric and heavy-tailed errors - Javier E. Contreras-Reyes; Rodrigo Wiff; Javier Soto; Carl R. Donovan; Miguel Araya (Environmental Biology of Fishes, 2021)

Involvement of dopaminergic signaling in the cross talk between the renin-angiotensin system and inflammation - Javier Campos; Rodrigo Pacheco (Seminars in Immunopathology, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Low Rate of Invasive Fungal Infections During Induction and Consolidation Chemotherapy for Adults with De Novo Acute Myeloid Leukemia Without Anti-mold Prophylaxis: Single-Center 2002–2018 Empirical/Pre-emptive Approach - Rodrigo Martino; Ana Garrido; Marta Santaliestra; Irene García-Cadenas; Silvana Novelli; Silvanna Daniella Saavedra; Albert Esquirol; Miquel Granell; Javier Briones; Carolina Moreno; Salut Brunet; Ana Giménez; et al. (Mycopathologia, 2020)

Trophic ecology of tadpoles in floodplain wetlands: combining gut contents, selectivity, and stable isotopes to study feeding segregation of syntopic species - Carolina Elisabet Antoniazzi; Javier Alejandro López; Rodrigo Ezequiel Lorenzón; Miguel Saigo; Melina Devercelli; Raúl Eduardo Maneyro Landó; Mercedes Rosa Marchese (Hydrobiologia, 2020)

Exploratory study on the presence of bisphenol A and bis(2-ethylhexyl) phthalate in the Santa Catarina River in Monterrey, N.L., Mexico - Arquímedes Cruz-López; René Alberto Dávila-Pórcel; Héctor de León-Gómez; Juan Manuel Rodríguez-Martínez; Santiago I. Suárez-Vázquez; Antonio Cardona-Benavides; Guillermo Javier Castro-Larragoitia; Lorenzo Boreselli; María de Lourdes Villalba; Adán Pinales-Munguía; Humberto Silva-Hidalgo; Rodrigo de la Garza; et al. (Environmental Monitoring and Assessment, 2020)

Pancreatic ductal adenocarcinomas from Mexican patients present a distinct genomic mutational pattern - Paulina Sanchez; Magali Espinosa; Vilma Maldonado; Rodrigo Barquera; Nayeli Belem-Gabiño; Javier Torres; Adrian Cravioto; Jorge Melendez-Zajgla (Molecular Biology Reports, 2020)

Endogenous, Climate, and Fishing Influences on the Population Dynamics of Small Pelagic Fish in the Southern Humboldt Current Ecosystem - T. Mariella Canales; Mauricio Lima; Rodrigo Wiff; Javier E. Contreras-Reyes; Ursula Cifuentes; José Montero (Frontiers in Marine Science, 2020)

Coping with exposure to hypoxia: modifications in stress parameters in gilthead seabream (Sparus aurata) fed spirulina (Arthrospira platensis) and brewer’s yeast (Saccharomyces cerevisiae) - Bruno Olivetti de Mattos; José Fernando López-Olmeda; Bartira Guerra-Santos; Cristóbal Espinosa Ruiz; José María García-Beltrán; Maria Ángeles-Esteban; Francisco Javier Sánchez-Vázquez; Rodrigo Fortes-Silva (Fish Physiology and Biochemistry, 2019)

De novo Assembly and Characterization of Patagonian Toothfish Transcriptome and Develop of EST-SSR Markers for Population Genetics - Jorge Touma; Killen Ko García; Scarleth Bravo; Francisco Leiva; Javier Moya; Luis Vargas-Chacoff; Alberto Reyes; Rodrigo Vidal (Frontiers in Marine Science, 2019)

Stereotyped seed preferences of the harvester ant Pogonomyrmex mendozanus in the central Monte desert - Maria Florencia Miretti; Javier Lopez de Casenave; Rodrigo G. Pol (Arthropod-Plant Interactions, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Anther and pollen development in sweet cherry (Prunus avium L.) in relation to winter dormancy - Erica Fadón; María Herrero; Javier Rodrigo (Protoplasma, 2019)

Spatial and temporal distribution of metals in PM2.5 during 2013: assessment of wind patterns to the impacts of geogenic and anthropogenic sources - Rodrigo Garza-Galindo; Ofelia Morton-Bermea; Elizabeth Hernández-Álvarez; Sara L. Ordoñez-Godínez; Omar Amador-Muñoz; Laura E. Beramendi-Orosco; Armando Retama; Javier Miranda; Irma Rosas-Pérez (Environmental Monitoring and Assessment, 2019)

ATLANTIC EPIPHYTES : a data set of vascular and non‐vascular epiphyte plants and lichens from the Atlantic Forest - Flavio Nunes Ramos; Sara Ribeiro Mortara; Nathalia Monalisa‐Francisco; João Pedro Costa Elias; Luiz Menini Neto; Leandro Freitas; Rodrigo Kersten; André Márcio Amorim; Fernando Bittencourt Matos; André Felippe Nunes‐Freitas; Suzana Alcantara; Marcia Helena Nagahama Alexandre; et al. (Ecology, 2019)
Epiphytes are hyper‐diverse and one of the frequently undervalued life forms in plant surveys and biodiversity inventories. Epiphytes of the Atlantic Forest, one of the most endangered ecosystems in the world, have high endemism and radiated recently in the Pliocene. We aimed to (1) compile an extensive Atlantic Forest data set on vascular, non‐vascular plants (including hemiepiphytes), and lichen epiphyte species occurrence and abundance; (2) describe the epiphyte distribution in the Atlantic Forest, in order to indicate future sampling efforts. Our work presents the first epiphyte data set with information on abundance and occurrence of epiphyte phorophyte species. All data compiled here come from three main sources provided by the authors: published sources (comprising peer‐reviewed articles, books, and theses), unpublished data, and herbarium data. We compiled a data set composed of 2,095 species, from 89,270 holo/hemiepiphyte records, in the Atlantic Forest of Brazil, Argentina, Paraguay, and Uruguay, recorded from 1824 to early 2018. Most of the records were from qualitative data (occurrence only, 88%), well distributed throughout the Atlantic Forest. For quantitative records, the most common sampling method was individual trees (71%), followed by plot sampling (19%), and transect sampling (10%). Angiosperms (81%) were the most frequently registered group, and Bromeliaceae and Orchidaceae were the families with the greatest number of records (27,272 and 21,945, respectively). Ferns and Lycophytes presented fewer records than Angiosperms, and Polypodiaceae were the most recorded family, and more concentrated in the Southern and Southeastern regions. Data on non‐vascular plants and lichens were scarce, with a few disjunct records concentrated in the Northeastern region of the Atlantic Forest. For all non‐vascular plant records, Lejeuneaceae, a family of liverworts, was the most recorded family. We hope that our effort to organize scattered epiphyte data help advance the knowledge of epiphyte ecology, as well as our understanding of macroecological and biogeographical patterns in the Atlantic Forest. No copyright restrictions are associated with the data set. Please cite this Ecology Data Paper if the data are used in publication and teaching events.

Is there a specific stage to rest? Morphological changes in flower primordia in relation to endodormancy in sweet cherry (Prunus avium L.) - Erica Fadón; Javier Rodrigo; Maria Herrero (Trees, 2018)

Atmospheric PM2.5 Mercury in the Metropolitan Area of Mexico City - Ofelia Morton-Bermea; Rodrigo Garza-Galindo; Elizabeth Hernández-Álvarez; Sara L. Ordoñez-Godínez; Omar Amador-Muñoz; Laura Beramendi-Orosco; Javier Miranda; Irma Rosas-Pérez (Bulletin of Environmental Contamination and Toxicology, 2018)

Seismic Parameters of Mining-Induced Aftershock Sequences for Re-entry Protocol Development - Javier A. Vallejos; Rodrigo A. Estay (Pure and Applied Geophysics, 2018)

Recognition of the importance of geogenic sources in the content of metals in PM2.5 collected in the Mexico City Metropolitan Area - Ofelia Morton-Bermea; Rodrigo Garza-Galindo; Elizabeth Hernández-Álvarez; Omar Amador-Muñoz; Maria Elena Garcia-Arreola; Sara L. Ordoñez-Godínez; Laura Beramendi-Orosco; Graciela L. Santos-Medina; Javier Miranda; Irma Rosas-Pérez (Environmental Monitoring and Assessment, 2018)

Diadenosine tetraphosphate (Ap4A) inhibits ATP-induced excitotoxicity: a neuroprotective strategy for traumatic spinal cord injury treatment - David Reigada; Rosa María Navarro-Ruiz; Marcos Javier Caballero-López; Ángela Del Águila; Teresa Muñoz-Galdeano; Rodrigo M. Maza; Manuel Nieto-Díaz (Purinergic Signalling, 2017)

Structural- and carotenoid-based throat colour patches in males of Lacerta schreiberi reflect different parasitic diseases - Megía-Palma Rodrigo; Martínez Javier; Merino Santiago (Behavioral Ecology and Sociobiology, 2016)

Scale-up of electrolytic and photoelectrolytic processes for water reclaiming: a preliminary study - María J. Martín de Vidales; Salvador Cotillas; José F. Perez-Serrano; Javier Llanos; Cristina Sáez; Pablo Cañizares; Manuel A. Rodrigo (Environmental Science and Pollution Research, 2016)

A structural colour ornament correlates positively with parasite load and body condition in an insular lizard species - Rodrigo Megía-Palma; Javier Martínez; Santiago Merino (The Science of Nature, 2016)

A Fast Method for the Segmentation of Synaptic Junctions and Mitochondria in Serial Electron Microscopic Images of the Brain - Pablo Márquez Neila; Luis Baumela; Juncal González-Soriano; Jose-Rodrigo Rodríguez; Javier DeFelipe; Ángel Merchán-Pérez (Neuroinformatics, 2016)

Dietary self-selection in fish: a new approach to studying fish nutrition and feeding behavior - Rodrigo Fortes da Silva; Alexandre Kitagawa; Francisco Javier Sánchez Vázquez (Reviews in Fish Biology and Fisheries, 2016)

Phylogenetic relationships of Isospora, Lankesterella, and Caryospora species (Apicomplexa: Eimeriidae) infecting lizards - Rodrigo Megía-Palma; Javier Martínez; Intissar Nasri; José Javier Cuervo; José Martín; Iván Acevedo; Josabel Belliure; Jesús Ortega; Roberto García-Roa; Slaheddine Selmi; Santiago Merino (Organisms Diversity & Evolution, 2016)

Replication of a chronic hepatitis B virus genotype F1b construct - Sergio Hernández; Gustavo Jiménez; Valentina Alarcón; Cristian Prieto; Francisca Muñoz; Constanza Riquelme; Mauricio Venegas; Javier Brahm; Alejandra Loyola; Rodrigo A Villanueva (Archives of Virology, 2016)

Uncertainty analysis in the financial assessment of an integrated management system for restaurant and catering waste in Spain - Neus Escobar; Javier Ribal; Gabriela Clemente; Alfredo Rodrigo; Andrés Pascual; Neus Sanjuán (The International Journal of Life Cycle Assessment, 2015)

Phylogeny of the reptilian Eimeria : are Choleoeimeria and Acroeimeria valid generic names? - Rodrigo Megía‐Palma; Javier Martínez; Iván Acevedo; José Martín; Roberto García‐Roa; Jesús Ortega; Marcos Peso‐Fernández; Gonzalo Albaladejo; Robert D. Cooper; Dhanashree A. Paranjpe; Barry R. Sinervo; Santiago Merino (Zoologica Scripta, 2015)
Reptiles are the animals with the most described coccidian species among all vertebrates. However, the co‐evolutionary relationships in this host–parasite system have been scarcely studied. Paperna & Landsberg ( South African Journal of Zoology , 24, 1989, 345) proposed the independent evolutionary origin of the Eimeria ‐like species isolated from reptiles based on morphological and developmental characteristics of their oocysts. Accordingly, they suggested the reclassification of these parasites in two new genera, Choleoeimeria and Acroeimeria . The validity of the genera proposed to classify reptilian Eimeria species remained unresolved due to the lack of species genetically characterized. In this study, we included 18S rRNA gene sequences from seven Eimeria ‐like species isolated from five different lizard host families. The phylogenetic analyses confirmed the independent evolutionary origin of the Eimeria ‐like species infecting lizards. Within this group, most species were placed into two monophyletic clades. One of them included the species with ellipsoidal oocysts (i.e. Choleoeimeria ‐like oocysts), whereas the species with more spheroidal oocysts (i.e. Acroeimeria ‐like oocysts) were included in the second one. This result supports the taxonomic validity of the genera Acroeimeria and Choleoeimeria .

Environmental Degradation in a Eutrophic Shallow Lake is not Simply Due to Abundance of Non-native Cyprinus carpio - Juan P. Ramírez-Herrejón; Norman Mercado-Silva; Eduardo F. Balart; Rodrigo Moncayo-Estrada; Valentín Mar-Silva; Javier Caraveo-Patiño (Environmental Management, 2015)

Uncertainty analysis in the environmental assessment of an integrated management system for restaurant and catering waste in Spain - Neus Escobar Lanzuela; Francisco Javier Ribal Sanchís; Alfredo Rodrigo Señer; Gabriela Clemente Polo; Andrés Pascual Vidal; Neus Sanjuán Pellicer (The International Journal of Life Cycle Assessment, 2015)

Molecular characterization of haemococcidia genus S chellackia (Apicomplexa) reveals the polyphyletic origin of the family Lankesterellidae - Rodrigo Megía‐Palma; Javier Martínez; Santiago Merino (Zoologica Scripta, 2014)
The current taxonomy on the haemococcidia establishes that the two genera of protozoan parasites that integrate the family Lankesterellidae are L ankesterella and S chellackia . However, the phylogeny of these genera, as well as the other coccidia, remains unresolved. In this sense, the use of type and described species is essential for the resolution of systematic conflicts. In this study, we molecularly characterize the type species of the genus S chellackia , that is, S . bolivari from Europe and also a described species of the same genus from Asia. At the same time, we contribute with the molecular characterization of another species of the genus L ankesterella . All this put together supports the polyphyly of the family Lankesterellidae. Therefore, we propose the resurrection of the zoological family, Schellackiidae Grassé , to include species within the genus S chellackia .

Chilean dolphins on the Argentine Atlantic coast - Annick Morgenthaler; Javier Fernández; Rodrigo Moraga; Carlos Olavarría (Marine Mammal Science, 2014)

Investigation of the Stable Atmospheric Boundary Layer at Halley Antarctica - Javier Sanz Rodrigo; Philip S. Anderson (Boundary-Layer Meteorology, 2013)

Evaluation of the antarctic surface wind climate from ERA reanalyses and RACMO2/ANT simulations based on automatic weather stations - Javier Sanz Rodrigo; Jean-Marie Buchlin; Jeroen van Beeck; Jan T. M. Lenaerts; Michiel R. van den Broeke (Climate Dynamics, 2013)

Lack of regeneration and climatic vulnerability to fire of Scots pine may induce vegetation shifts at the southern edge of its distribution - Albert Vilà‐Cabrera; Anselm Rodrigo; Jordi Martínez‐Vilalta; Javier Retana (Journal of Biogeography, 2012)
Aim Forest ecosystems dominated by fire‐sensitive species could suffer shifts in composition under altered crown fire regimes mediated by climate change. The aims of this study were to: (1) study the spatio‐temporal patterns and the climatic distribution of fires in Scots pine ( Pinus sylvestris ) forests during the last 31 years in north‐eastern Spain, (2) evaluate the climatic vulnerability to fire of these forests in Spain, (3) analyse the regeneration of Scots pine after fire, and (4) predict the mid‐term maintenance or replacement of Scots pine in burned areas. Location Catalonia (north‐eastern Spain): the southern distribution limit of Scots pine. Methods We characterized the spatio‐temporal and the climatic distribution of fires that occurred in Catalonia between 1979 and 2009. We used a generalized linear model to characterize the climatic vulnerability to fire of Scots pine in the whole of Spain. We assessed the regeneration of the species after crown fires in nine burned areas in Catalonia. The resulting data were integrated into a stochastic matrix model to predict the mid‐term maintenance or replacement of Scots pine in burned areas. Results During the last three decades, Scots pine forests distributed in dry sites were most affected by fire. Our assessment of the vulnerability to fire of Scots pine forests in Spain as a whole, based on climatic and topographical variables, showed that 32% of these forests are vulnerable to fire, and that this proportion could increase to 66% under a conservative climate change scenario. Field data showed almost no regeneration of Scots pine after crown fires, and a limited capacity to recolonize from unburned edges, even in relatively old fires, with 90% of recruits located in the first 25 m from the edge. This process could be delayed by the elapsed time for new recruits to achieve reproductive maturity, which we estimated to be c. 15 years. Finally, our matrix model predicted the replacement of burned Scots pine forests by oak ( Quercus sp.) forests, shrublands or mixed resprouter forests. Main conclusions Increased vulnerability to fire of Scots pine forests under future, warmer conditions may result in vegetation shifts at the southern edge of the distribution of the species.

Flower bud differentiation and development in fruiting and non-fruiting shoots in relation to fruit set in apricot (Prunus armeniaca L.) - Carme Julian; Maria Herrero; Javier Rodrigo (Trees, 2010)

Arrival date and territorial behavior are associated with corticosterone metabolite levels in a migratory bird - Elisa Lobato; Juan Moreno; Santiago Merino; Judith Morales; Gustavo Tomás; Javier Martínez; Rodrigo A. Vásquez; Alexandra Kuchar; Erich Möstl; José Luis Osorno (Journal of Ornithology, 2010)

Conservation Challenges for the Austral and Neotropical America Section - GERARDO CEBALLOS; MARIANA M. VALE; CRISTIAN BONACIC; JULIO CALVO‐ALVARADO; RURIK LIST; NORA BYNUM; RODRIGO A. MEDELLÍN; JAVIER A. SIMONETTI; JON PAUL RODRÍGUEZ (Conservation Biology, 2009)
The Austral and Neotropical America (ANA) section of the Society for Conservation Biology includes a vast territory with some of the largest relatively pristine ecosystems in the world. With more than 573 million people, the economic growth of the region still depends strongly on natural resource exploitation and still has high rates of environmental degradation and biodiversity loss. A survey among the ANA section membership, with more than 700 members, including most of the section's prominent ecologists and conservationists, indicates that lack of capacity building for conservation, corruption, and threats such as deforestation and illegal trade of species, are among the most urgent problems that need to be addressed to improve conservation in the region. There are, however, strong universities and ecology groups taking the lead in environmental research and conservation, a most important issue to enhance the ability of the region to solve conservation and development conflicts .

Prevalence of hepatitis B virus genotypes in chronic carriers in Santiago, Chile - Mauricio Venegas; Gabriela Muñoz; Carmen Hurtado; Luis Alvarez; Marta Velasco; Rodrigo A. Villanueva; Javier Brahm (Archives of Virology, 2008)

Post‐fire recovery of Mediterranean ground ant communities follows vegetation and dryness gradients - Xavier Arnan; Anselm Rodrigo; Javier Retana (Journal of Biogeography, 2006)
Aim In the Mediterranean Basin, the main forest communities vary in their ability to recover after fire. In this study we analyse the effects of fire on ant communities occurring in various vegetation types distributed along a geographical gradient in the western Mediterranean region. Location The study was carried out in burned and unburned habitats of 22 sites corresponding to eight vegetation types distributed along a gradient of dryness throughout Catalonia (north‐east Spain). Methods We placed five pairs of plots (one plot located in the burned area and the second one placed in the unburned margin) per site. We compared ant communities in these unburned and burned plot types 8 years after fire using pitfall traps. Traps were set out in mid‐May and mid‐July. We analysed the structure and composition of ant communities in the burned and unburned areas of these vegetation types using anova tests, correspondence analysis (CA) and linear regression. Results The resilience of ant communities varies with vegetation type. Ant communities in forests with high resilience also recover rapidly after fire, while those in forests that do not recover after fire show the lowest resilience. Species richness does not depend on burning or vegetation type. The resilience of these Mediterranean ant communities to fire is related to the environmental characteristics of the region where they live. Accordingly, differences between burned and unburned habitats are smaller for ant communities in areas with higher water deficit in summer than for those in moister ones. Main conclusions The structure and composition of ant communities after fire depends on the level of direct mortality caused by the fire. It affects ant species differently, as determined by the habitats used for nesting and foraging. The reestablishment of vegetation cover depends on forest composition before the fire. As vegetation cover determines resource and microhabitat availability and competitive relationships among species, forest composition before the fire also affects post‐fire recovery of ant communities to the medium‐term. Finally, ant communities living in drier areas recover more quickly after fire than those living in moister ones. This pattern might be because in areas with higher water deficit there are more species characteristic of open environments, which are habitats similar to those generated after fire.

Predicting the Recovery of Pinus halepensis and Quercus ilex Forests after a Large Wildfire in Northeastern Spain - Maria José Broncano; Javier Retana; Anselm Rodrigo (Plant Ecology, 2005)

Activity Patterns of Harvester Ants Pogonomyrmex pronotalis and Pogonomyrmex rastratus in the Central Monte Desert, Argentina - Rodrigo Pol; Javier Lopez de Casenave (Journal of Insect Behavior, 2004)

Fire and species range in Mediterranean landscapes: an experimental comparison of seed and seedling performance among Centaurea taxa - Miquel Riba; Anselm Rodrigo; Bruno Colas; Javier Retana (Journal of Biogeography, 2002)
Aim Fire is a major disturbance event in Mediterranean landscapes. In this paper, we experimentally assess the effects of fire and post‐fire conditions on seed germination and establishment of twenty Centaurea taxa to test whether differences among taxa are associated with range size. Methods The taxa (species and subspecies) considered were classified as rare and widespread according to their `area of occupancy' in the Mediterranean coast of Spain and France. In a first experiment, we analyse the effects of heat‐shock (particularly, room temperature, 70 and 110 °C) on percentage germination and speed of germination (T50). In a second experiment, we analyse the effects of post‐fire conditions (shading and soil type: burned/unburned) on seed germination and establishment ability. Results Temperatures over 120 °C resulted in 100% mortality, while temperatures in the range of those expected to be found in the first centimetres down the soil profile during a wildfire (70–110 °C) had no effect on seed germination. Differences in germination percentage and T50 among taxa were not related to rarity. In the post‐fire conditions experiment, decreased radiation (shading) increased percentage germination and T50 in most taxa, while burned soil decreased germination in some of them. The effects of post‐fire conditions on seedling growth (number of leaves and leaf size) were also different among taxa, but such differences were not related to rarity. However, rarity was associated with low establishment ability, as rare taxa tended to show smaller seedling size and higher mortality rates under the whole range of conditions tested. Main conclusions The results obtained indicate that fire has a negative effect upon the survival of populations in all the taxa considered, and that rare‐common differences in germination and seedling establishment are not directly related to disturbance by fire. As far as interspecific differences in range size are concerned, other factors, either alone or in combination with a low regeneration ability after fire, need to be explored further.